Sociocultural and perceived public image of nurses among nursing students: the mediating role of self-concept - Lailani Sacgaca; Eddieson Pasay an; Aida Sanad Alqarni; Petelyne Pangket; Salman Amish Alshammari; Magda Yousif Ramadan; Ameera Khaled Alonezei; Fatmah Ahmed Alamoudi; Insaf Hassan Ahmed Mohammed; Dolores Cabansag; Lizy Sonia Benjamin (BMC Nursing, 2024)
Abstract Background Studying the public perception of nurses among nursing students is vital in establishing strategic solutions to recruit and retain more students in nursing programs and to contain nurses in the health care system. Aim This study aimed to determine the mediating role of self-concept in the relationship between sociocultural and perceived public image of nurses. Methods This study employed a correlational approach using convenience sampling of 1390 participants. This study was conducted at six large universities in three regions of Saudi Arabia (central, northern, and eastern). Student nurses in their second to fourth years of study were included as participants, with an 89.7% response rate. Data were collected from January to April 2023. Results A significant positive relationship was observed between sociocultural factors and self-concept (r = .685, p = .0001). In addition, there was a significant positive relationship between self-concept and public image (PI) (r = .352, p value = 0.0001). Furthermore, there was a significant positive relationship between sociocultural and public image (r = .456, p = .0001); sociocultural had a direct effect on self-concept (β = 0.324, SE = 0.098, t = 9.429, p < .0001) and public image (β = 0.605, SE = 0.038, t = 22.617, p < .0001). Furthermore, sociocultural had an indirect effect on public image through self-concept (H6) (β = 0.389, SE = 0.123, t = 12.766, p < .0001). Discussion The study findings suggest that nursing school programs should take measures to foster a supportive environment that promotes self-concept and public image, while also being mindful of the sociocultural background. This would also open the scope for further research on the matter involving multiple centers. Conclusions This study suggests the need for programs to boost self-concept and public image that consider sociocultural influences. These ’findings have crucial implications for student nurses’ social and psychological wellbeing as they improve the understanding of how sociocultural affects self-concept and public image.